An evaluation of the distribution properties, factor structure, and item response profile of an assessment of emotion recognition. Issue 3 (March 2020) - McKenzie, Karen; Murray, Aja; Murray, Kara; O'Donnell, Michael; Murray, George C.; Metcalfe, Dale; McCarty, Kristofor
Abstract: Many people with developmental disabilities, such as autism spectrum disorder and intellectual disability have emotion recognition (ER) difficulties compared with typically developing (TD) peers. Accurate assessment of the extent and nature of differences in ER requires an understanding of the response profiles to ER assessment stimuli. We analysed data from 504 TD individuals in response to an ER assessment in respect of distribution properties, factor structure, and item response profile. Eighteen emotion items discriminated better at lower levels of ER ability in TD participants. Neutral expressions were the hardest to interpret; surprise, anger, happy, and bored were easiest. The amount of contextual information in combination with the emotion being depicted also appeared to influence level of difficulty. Similar psychometric research is needed with people with developmental disabilities. Abstract : Psychology; Assessment; Autism spectrum disorder; Emotion recognition; Item response profile; Intellectual disability